Brazilian marine sport fishing legislation: starting point for maintaining the quality of fish stocks (Research, Society and Development, 2020)
Marine sport fishing in Brazil is expanding. Although apparently it causes less impact than other fishing sectors, its potential negative effect on target populations and the ecosystem is known. The regulation of sport fishing can be a starting point, so that it can be done in an orderly and sustainable manner. This paper compares the Brazilian legislation focused on marine sport fishing with that of Australia, Canada and the United States, countries that have specific legislation and significant advances to organize this activity. This organization is very important, as recreational fishing has a high financial return. This comparison was made given the shortage of guiding legislation in Brazil, pointing out modifications in the Brazilian legislation for marine sport fishing, which may be beneficial to the activity in the country, given the current scenario of growth and overexploitation of some fish stocks along the Brazilian coast.